2009
DOI: 10.1097/nen.0b013e3181af2e46
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Alzheimer Disease and Tauopathy-Related Genes in Postmortem Brain

Abstract: DNA methylation occurs predominantly at cytosines that precede guanines in dinucleotide CpG sites; it is one of the most important mechanisms for epigenetic DNA regulation during normal development and for aberrant DNA in cancer. To determine the feasibility of DNA methylation studies in the postmortem human brain, we evaluated brain samples with variable postmortem artificially increased delays up to 48 hours. DNA methylation was analyzed in selected regions of MAPT, APP, and PSEN1 in the frontal cortex and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 53 publications
6
118
1
2
Order By: Relevance
“…However, several studies have focused on individual risk genes to determine disease-related DNA methylation differences. No significant differences were detected in methylation levels of MAPT, APP, and PSEN1 in postmortem brain from AD and FTLD-spectrum cases [69]; however, significant differences in GRN methylation levels were detected, with the GRN promoter hypermethylated in FTD vs controls (61.5 % vs 46.3 %) [75]. The G 4 C 2 repeat expansion in the C9ORF72 gene is a common cause of ALS and FTLD [19].…”
Section: Dna Methylation-based Therapymentioning
confidence: 93%
See 1 more Smart Citation
“…However, several studies have focused on individual risk genes to determine disease-related DNA methylation differences. No significant differences were detected in methylation levels of MAPT, APP, and PSEN1 in postmortem brain from AD and FTLD-spectrum cases [69]; however, significant differences in GRN methylation levels were detected, with the GRN promoter hypermethylated in FTD vs controls (61.5 % vs 46.3 %) [75]. The G 4 C 2 repeat expansion in the C9ORF72 gene is a common cause of ALS and FTLD [19].…”
Section: Dna Methylation-based Therapymentioning
confidence: 93%
“…Genes associated with Mendelian forms of dementia, such as APP, PSEN1, and MAPT, showed no clear differences in DNA methylation between AD patients and controls in multiple studies [44,69,70], and high-throughput studies have failed to detect large differences in methylation profiles between cases and controls [71]. However, small differences in DNA methylation along with age-related epigenetic drift may play a role in AD risk over time.…”
Section: Dna Methylation-based Therapymentioning
confidence: 99%
“…However, in later studies, no difference was found in methylation of selected regions of the APP gene in various stages of AD progression compared with controls. 51 Further, the methylation status of the APP promoter region does not indicate involvement in regulation of this gene in AD. 56 A study by Bakulski et al 57 was the first to provide a semi-unbiased, quantitative, genome-wide localization of DNA epigenetic differences in the human frontal cortex between AD cases and controls.…”
Section: Epigenetic Alterations In Ad Dna Methylationmentioning
confidence: 99%
“…In one of these studies, DNA methylation at the 5′ promoter regions of a few candidate genes was investigated. 51 These genes were selected on the basis of hypotheses concerning the molecular mechanisms of AD, and included microtubule-associated protein tau, APP, and presenilin-1 genes in the frontal cortex and hippocampi of both controls and AD cases at different Braak stages. No significant difference in CpG methylation was observed between the control and pathological samples.…”
Section: Epigenetic Alterations In Ad Dna Methylationmentioning
confidence: 99%
“…However, studies in human PD cases did not detect any difference in methylation of the parkin promoter, downplaying its significance in PD [47]. Similarly, the promoter of the deubiquitinating enzyme ubiquitin carboxy-terminal hydrolase L1 (UCHL1 ), another recessive PD-linked gene, is hypermethylated in cancer, but not differentially methylated in brain samples from PD patients [48]. In the same study, the methylation profiles of the MAPT promoter in the frontal cortex and hippocampus of subjects with Alzheimer's disease, PD or tauopathies or synucleinopathies contained no differences compared to controls.…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 97%